Biochars from Spirulina as an alternative material in the purification of lactic acid from a fermentation broth - Piloni, Roxana Verónica; Fontes Coelho, Luciana [UNESP]; Sass, Daiane Cristina [UNESP]; Lanteri, Mario; Zaghete Bertochi, Maria Aparecida [UNESP]; Laura Moyano, E.; Contiero, Jonas [UNESP] (Elsevier, 2021)
In this study, Spirulina biochar obtained from fast pyrolysis was evaluated as an alternative to commercial activated carbon for lactic acid (LA) purification from a fermentation broth. Thermally (350 and 400 ​°C treatment of the biochar in N2 atmosphere for 4 ​h) and chemically (KOH solution impregnation of the algal material and fast pyrolysis to obtain the biochar) activated Spirulina biochars were also tested. The biochars were previously characterized using SEM and FT-IR. Two purification methodologies were evaluated: filtration and stirring. The stirring method prove to be simpler, faster and chipper, with excellent purification results. All the evaluated biochars presented a performance comparable to that of activated carbon in the stirring methodology. Spirulina biochar and the KOH activated biochar were the once with the best results, with 92 and 82% LA recovery and 82 and 90% protein removal efficiencies, respectively.
Keywords: Biochar; Fast pyrolysis; Fermentation; Lactic acid; Spirulina